Pendekatan Model Pembelajaran Flipped Classroom Dengan Media Video Interaktif Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Stoikiometri Di SMA Negeri 3 Manado - Antara, Marcho Mangi; Tani, Djefri; Kumajas, Jenny (General Chemistry Journal, 2023)
The purpose of this study was to improve student learning outcomes on stoichiometry by using a flipped classroom learning model with interactive video media at SMA Negeri 3 Manado. The research conducted was a quantitative study using a quasi-experimental design, a study using two groups, there was an experimental group and a control group to find out the significant difference between the two groups after treatment. Prior to the treatment, students were given an initial test (pretest) and after the treatment, students were given a final test (posttest). The population in this study were all class X.IPA SMA Negeri 3 Manado and the sample consisted of 2 classes, namely class X IPA 1 as the experimental class and class X IPA 5 as the control class, each consisting of 27 people. The data collection technique used in this study is using a test, the test in this case is the pretest and posttest. Based on the research data, the results of the t-test analysis at the significance level (α) = 0.05 were obtained: tcount = 4.87 and ttable = 2.0066, with the N-Gain test for the experimental class of 0.65.and the control.class 0.36. So it can be concluded that there are differences in student learning outcomes using the flipped classroom learning model with interactive video media on stoichiometry material at SMA Negeri 3 Manado.